Кіберфізичні системи та їх програмне забезпечення - Чунжі, Ван; Яцишин, С. П.; Лиса, О. В.; Мідик, А.-В. В. (Видавництво Львівської політехніки, 2018)
У зв’язку зі швидким розвитком кіберфізичних систем істотну увагу в світі звертають на різні аспекти їх формування й експлуатації. У 2014 р. NIST, USA створила Громадську робочу групу кіберфізичних систем для об’єднання широкого кола фахівців на відкритому громадському форумі, щоб допомогти визначити та сформувати їхні основні характеристики для керівництва розробленням та впровадженням «інтелектуальних» програм у різних сферах, серед яких розумні виробництво, транспортування, енергетика та охорона здоров’я. Важливим вважається питання програмного забезпечення, оскільки, по-перше, вказані системи складаються із великої, нерегламентованої кількості компонентів, рознесених у просторі й часі, а, по-друге, компоненти систем мають змогу самостійно, під власні потреби, додатково встановлювати необхідне програмне забезпечення, відоме як Middleware.

In connection with the enhanced development of cyber-physical systems, considerable attention in the world is given to various aspects of their formation and operation. So in 2014, NIST, USA has created a Cyber-Physical System (further CPS) Community Working Group to bring together a wide range of professionals at an open, public forum to help identify and shape the main characteristics of the CPS to guide the design and implementation of «intelligent» programs in various areas, including smart production, transportation, energy and healthcare. By analyzing the known CPSs, their metrological and software, we can evidence that their number is steadily increasing, and the scope of application is expanding. Software and metrological assurance develop in the direction of supporting the work of existing CPSs as also and in the design of their suitability for new types of CPSs. Therefore, the requirements for creating a CPS are security, confidentiality, reliability, stability, guarantees for common interconnected devices and infrastructures, dynamism, compatibility (the ability to host different computing models), the support of different modes of communication in the network, the solvability of complexity problems ( problems of accessing the obtained data and control with feedback in any architecture of the CPS), synchronization, interaction with the operating environment, the ability to cooperate with each other for the creation of the complex effects, the creation of effects that exceeds the sum of the effects of individual parts of the CPS, the ability to combine several goals. CPSs are characterized by well-defined components: with known performance described by using standardized semantics and syntax. CPSs must support the flexibility of applications and domains. To realize this, the definition of components must be flexible and open. The architecture should support an accurate questioning of components in order to provide flexibility in the creation and adaptation of virtual systems and the promotion of innovation. The CPS should support a large scale of sizes, complexity and loading in addition. The components should be integrated or/and scaled quickly, even while operating. The CPS architecture should consist of independent, disconnected components for flexibility, reliability and resilience to changing situations. The solution must also exist between the architectural layers, allowing each layer to be changed, without affecting other layers. In order for the system to integrate different components, the interfaces to these components should be based on interpreted and unambiguous standards. Adaptation is achieved through the flexibility of internal components and interoperability. An important issue is software, since, firstly, these systems consist of a large, unregulated number of components spaced apart in space and time, and secondly, system components are able to independently install themselves for their own needs the required software denominated asMiddleware.
Cyber-physical systems and their software
Keywords: кіберфізичні системи; смарт-засоби; програмне забезпечення; проміжне програмне забезпечення; cyber-physical systems; smart means; software; middleware